An improved polymerase chain reaction-restriction fragment length polymorphism assay for the detection of a PON2 gene polymorphism - DUAN, XIAORAN (Biomed Rep, 2016)
In recent research, it has been shown that there have been variants of rs12026 within the paraoxonase 2 (PON2) gene, which have been associated with cardiovascular disease, cerebrovascular disease, diabetes and other diseases. The isochizomers, such as the BsoFI enzyme, required for the detection of this polymorphism are expensive. Therefore, an improved and less expensive polymerase chain reaction (PCR)-restriction fragment length polymorphism method was established for the detection of the single-nucleotide polymorphism rs12026 in the exon 5 of chromosome 7 of the human PON2 gene using the method of amplification-created restriction site. Subsequent to assessing 302 individuals, the genotype frequencies were 68.9% for CC, 29.8% for CG and 1.3% for GG, and the allelic frequencies were 83.8% for C and 16.2% for G. The PCR results were confirmed by DNA sequencing. The χ(2) test showed that the genotype and allele frequencies of PON2-148 do not deviate from Hardy-Weinberg equilibrium, and the sequences of amplified products were consistent with the sequence published in GenBank with the exception of a mismatched base.